1985
DOI: 10.1126/science.2408336
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Immunogenicity of the Pre-S Region of Hepatitis B Surface Antigen

Abstract: The 55 codons upstream of the gene sequence encoding the hepatitis B surface antigen (HBsAg) are called the pre-S(2) region. It has been proposed that polypeptides of high molecular weight that contain the pre-S(2) region should be included in future hepatitis B virus (HBV) vaccines. The pre-S(2) region and the S gene product [25 kilodalton (kD)] together compose a polypeptide of high molecular weight (33 kD). As an initial attempt to determine the relevance of the 33-kD polypeptide to development of an HBV va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
116
0
2

Year Published

1986
1986
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(123 citation statements)
references
References 21 publications
5
116
0
2
Order By: Relevance
“…It has been claimed that the HBV pre-S2 region (Milich et al, 1985;Valenzuela et al, 1985) enhances the immunogenicity of the HBsAg. A recombinant baculovirus (AcNPV-PsSYK27) has therefore been constructed containing the coding region of the pre-S2 region (55 amino acids) as well as the HBsAg gene.…”
Section: Discussionmentioning
confidence: 99%
“…It has been claimed that the HBV pre-S2 region (Milich et al, 1985;Valenzuela et al, 1985) enhances the immunogenicity of the HBsAg. A recombinant baculovirus (AcNPV-PsSYK27) has therefore been constructed containing the coding region of the pre-S2 region (55 amino acids) as well as the HBsAg gene.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results indicate that the pre-S(2) region of the HBsAg overcame the nonresponsiveness of B-cell epitopes of the S region and may serve as a T-helper cell epitope. Enhanced immunogenicity of the S region by preimmunization with pre-S protein has been shown by Milich et al (17,18) in inbred strains of mice. They show that preimmunization with pre-S protein of mice nonresponsive to S protein results in an enhanced response to S protein after reimmunization with HBsAg containing both proteins.…”
Section: Resultsmentioning
confidence: 89%
“…The majority of such cell constructs use recombinants containing a part of the HBV genome coding for the HBsAg only. Since the pre-S2 region may protect from HBV infection in chimpanzees (Itoh et al, 1986), and have enhanced immunogenicity in animals (Milich et al, 1985; et al., 1985), the inclusion of pre-S2 protein seems preferable. Electrophoretic and pHSA binding analyses showed that the pre-S2 protein was indeed included in the HBsAg particles released from MS128 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The other, called large S (P39/GP42), contains an extra 108 amino acids (pre-S1) at the amino terminus of middle S. Pre-S proteins are thought to be involved in virus attachment to hepatocytes (Machida et al, 1983;Neurath et aL, 1986) and in enhanced immunogenicity (Milich et al, 1985;Neurath et al, 1985). Therefore, much attention has been focused upon the role of pre-S proteins in HBV infection.…”
Section: Introductionmentioning
confidence: 99%